Effect of gain medium on the performance of brillouin fiber laser - Ahmad, Harith; Parvizi, R.; Shahabuddin, N.S.; Yusoff, Z.; Harun, Sulaiman Wadi (John Wiley & Sons, 2010)
The performance of single-wavelength Brillouin fiber lasers (BFLs) is investigated for different gain medium. An efficient BFL is demonstrated using a piece of 100-m-long PCF as the gain medium. The BFL provides a peak power of 0 am and a side mode suppression ratio of more than 30 dB with the threshold power of 8.5 dBm for the BFL generation. However, the threshold is much lower for the BFL configured with 20 km long non-zero dispersion shifted fiber, which has a smaller core size. With this fiber, the threshold power of the BFL is obtained at 5 am, and this power increases with the shorter length of the gain medium. (C) 2010 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52: 2158-2160, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.25386